Education through Chess and Physical Movement in the Primary School - Mihaela Butnariu (Editura Universitatii Transilvania din Brasov, 2022)
Considering that chess is a game of perspective, which develops logical thinking, imagination, anticipation capacity, and vision in space, the purpose of this paper is to teach students to move chess pieces correctly, to think of two or more consecutive moves, to develop a more detailed overview of the pieces in the game. Although chess is static, with no motorsport, we will try to change this game into a dynamic one, turning children into chess pieces. They will perform, on a surface drawn on the ground in the form of a chessboard, the movement corresponding to the piece they represent in the respective move by different variants of jumping from the initial position to the final position, respecting the rules of the game of chess. Thus, we turn the game of chess into a dynamic and funny game, played on teams.